2016
DOI: 10.1037/a0038456
|View full text |Cite
|
Sign up to set email alerts
|

Validating the voodoo doll task as a proxy for aggressive parenting behavior.

Abstract: Objective Six studies (N = 1,081 general population parents) assessed the validity of the Voodoo Doll Task (VDT) as a proxy for aggressive parenting behaviors. Methods Participants were given an opportunity to symbolically inflict harm by choosing to stick “pins” into a doll representing their child. Results Individual differences in parents’ trait aggression (Studies 1, 2, and 6), state hostility (Study 3), attitudes towards the corporal punishment of children (Study 4), self-control (Study 6), depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 36 publications
4
29
1
Order By: Relevance
“…First, parents completed several paper-and-pencil questionnaires that assessed constructs relevant to CPA: The Center for Epidemiological Studies Depression Scale, the Buss-Perry Aggression Questionnaire (Buss & Perry, 1992), and the Self-Control Scale (Tangney, Baumeister, & Boone, 2004). These measures are unrelated to the current research, but are reported in McCarthy et al (2016).…”
Section: Main Studymentioning
confidence: 94%
See 4 more Smart Citations
“…First, parents completed several paper-and-pencil questionnaires that assessed constructs relevant to CPA: The Center for Epidemiological Studies Depression Scale, the Buss-Perry Aggression Questionnaire (Buss & Perry, 1992), and the Self-Control Scale (Tangney, Baumeister, & Boone, 2004). These measures are unrelated to the current research, but are reported in McCarthy et al (2016).…”
Section: Main Studymentioning
confidence: 94%
“…Parents ( N = 197) who engaged in the main study were the same as those in Study 6 of McCarthy et al (2016); however, results from analyses described herein have not been published before. One person reported they were a non-parent at the time of the study and their data were omitted from analyses.…”
Section: Main Studymentioning
confidence: 99%
See 3 more Smart Citations